Muslim Role Model from Khabib Nurmagomedov as A Muslim Athlete in The UFC World - Yazid, Abdul; Muvid, Muhamad Basyrul (Abdurrauf Journal of Islamic Studies, 2024)
This research explores Khabib Nurmagomedov's role as a Muslim athlete in the UFC and its impact on the image of Islam among UFC fans and the global community. Using explanatory qualitative research methods, this research analyzes interview content, career journey case studies, participant observation, and document analysis related to Khabib. The findings show that Khabib has succeeded in creating a positive image of Muslim athletes, providing inspiration and empowerment for the Muslim community, and having a positive influence on the perception of Islam. Its presence also supports the promotion of diversity and acceptance in the world of sport. The media plays an important role in disseminating a positive image of Islam through coverage that highlights Islamic values ??and Khabib's success. This research confirms that Khabib's role not only created a legacy in sports history, but also had a profound impact in changing society's view of Islam in the global sports arena. [Abstrak: Penelitian ini mengeksplorasi peran Khabib Nurmagomedov sebagai atlet Muslim di UFC dan dampaknya terhadap citra Islam di kalangan penggemar UFC dan masyarakat global. Melalui metode penelitian kualitatif eksplanatori, penelitian ini menganalisis konten wawancara, studi kasus perjalanan karier, pengamatan partisipatif, dan analisis dokumen terkait Khabib. Temuan menunjukkan bahwa Khabib berhasil menciptakan pencitraan positif atlet Muslim, memberikan inspirasi dan pemberdayaan bagi komunitas Muslim, serta memberikan pengaruh positif pada persepsi Islam. Kehadirannya juga mendukung promosi kebhinekaan dan penerimaan dalam dunia olahraga. Media memainkan peran penting dalam menyosialisasikan gambaran positif tentang Islam melalui liputan yang menyoroti nilai-nilai keislaman dan keberhasilan Khabib. Penelitian ini mengkonfirmasi bahwa peran Khabib tidak hanya menciptakan warisan dalam sejarah olahraga, tetapi juga memiliki dampak mendalam dalam mengubah pandangan masyarakat terhadap Islam di ranah olahraga global.]